2019
DOI: 10.1002/ece3.5355
|View full text |Cite
|
Sign up to set email alerts
|

Harvest effects on density and biomass of Neopicrorhiza scrophulariiflora vary along environmental gradients in the Nepalese Himalayas

Abstract: A surprisingly large number of species potentially threatened by human harvest lack quantitative ecological studies incorporating harvest effects, especially clonal species in the alpine Himalayas. We studied density and biomass variation of a threatened medicinal herb, Neopicrorhiza scrophulariiflora, to examine the effect of harvest on plant performance. The study covered two regions with contrasting harvest situations—one with open‐access and another protected from commercial harvesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…The prevailing disturbance practices (grazing, trampling, and overexploitation) and lack of awareness of the population ecology and the conservation status of the plant are the major challenges for sustainable management at the unprotected site (Pouliot et al, 2018). This is also in agreement with Poudeyal et al (2019) who observed that intense human disturbances, especially harvest, played a crucial role as determinants of the density and structure of Neopicrorhiza scrophulariiflora populations.…”
Section: Effects Of Different Environmental Variables On the Density Of Different Stagessupporting
confidence: 72%
“…The prevailing disturbance practices (grazing, trampling, and overexploitation) and lack of awareness of the population ecology and the conservation status of the plant are the major challenges for sustainable management at the unprotected site (Pouliot et al, 2018). This is also in agreement with Poudeyal et al (2019) who observed that intense human disturbances, especially harvest, played a crucial role as determinants of the density and structure of Neopicrorhiza scrophulariiflora populations.…”
Section: Effects Of Different Environmental Variables On the Density Of Different Stagessupporting
confidence: 72%
“…Illegal trade across the borders attributed to the declining population of medicinal plants (Pyakurel et al 2017, Kunwar et al 2020). Premature collection and overharvesting of medicinal plants are common practice in Nepal (Ghimire and Aumeeruddy‐Thomas 2005, Pyakurel et al 2018, Poudeyal et al 2019, Kunwar et al 2021). Local harvesters usually collect whole populations by uprooting them.…”
Section: Discussionmentioning
confidence: 99%
“…These measurements of plants in their wild habitats help researchers for deciding plant-to-plant distance for maximizing plant biomass yield under Good Agriculture Practice (GAP) recently (Poudeyal et al, 2019;Saha and Basak, 2020;Ierna et al, 2020) in medicinal and aromatic plants to supply to pharmaceutical industries for producing plant-based medicine molecules and drugs.…”
Section: Plant Morphological Characteristicsmentioning
confidence: 99%